(untitled) (Prithvi Academic Journal, 2023)
Molecular dynamics simulation is used to estimate the melting point of cobalt using the embedded atomic model (EAM) potential by heat until melting, void, hysteresis and interface methods. For instance, the estimated melting temperature are 2102 K, 1944.15 K, 1731 K and 1725±25 K using these methods, respectively. Then, the melting points at different pressures are calculated. A graph depicting the variation of melting point with pressure is drawn and compared with the available simulation and experimental results. The melting point at a low-pressure range is similar to the previous diamond anvil cell experiments. Besides, using the Simon equation, we calculated the melting slope at 0 GPa pressure of 36 K/GPa for one phase and 40 K/GPa for two-phase methods.